Clinical efficacy of new aloe vera- and myrrh-based oral mucoadhesive gels in the management of minor recurrent aphthous stomatitis: a randomized, double-blind, vehicle-controlled study - Mansour, Ghada; Ouda, Soliman; Shaker, Ahmed; Abdallah, Hossam M. (Journal of oral pathology & medicine, 2014)
Objective To evaluate the clinical efficacy, and safety of newly customized natural oral mucoadhesive gels, containing either aloe vera or myrrh as active ingredients, in the management of minor recurrent aphthous stomatitis (MiRAS). Subjects and Methods Ninety subjects with MiRAS were recruited from Oral Medicine Clinic, at Faculty of Dentistry, King Abdulaziz University, Saudi Arabia, for this randomized, double‐blind, placebo‐controlled study. Two new natural gels, containing aloe vera and myrrh, were prepared in a concentration of (0.5% w/w), in addition to a plain mucoadhesive gel used as a placebo. Patients with fresh ulcers (<48‐h duration) were instructed to apply either one of the three gels four times a day for a period of 5 days. Clinical efficacy was investigated in the form of changes in ulcer size, pain intensity, erythema, and exudation at days 4 and 6 of study entry. Participants were interviewed for the emergence of any side effects. Results 76.6% of patients using aloe gel showed complete ulcer healing, 86.7%, and 80% of them revealed subsidence of erythema and exudation, respectively, especially at day 6 visit, whereas 76.7% of myrrh‐treated patients revealed almost absence of pain at day 6. No side effects were encountered with the use of any of the three gels. Conclusion The new formulated aloe‐ and myrrh‐based gels proved to be effective in topical management of MiRAS. Aloe was superior in decreasing ulcer size, erythema, and exudation; whereas myrrh resulted in more pain reduction.